2021
DOI: 10.1073/pnas.2105838118
|View full text |Cite
|
Sign up to set email alerts
|

Specific electromagnetic radiation in the wireless signal range increases wakefulness in mice

Abstract: Electromagnetic radiation (EMR) in the environment has increased sharply in recent decades. The effect of environmental EMR on living organisms remains poorly characterized. Here, we report the impact of wireless-range EMR on the sleep architecture of mouse. Prolonged exposure to 2.4-GHz EMR modulated by 100-Hz square pulses at a nonthermal output level results in markedly increased time of wakefulness in mice. These mice display corresponding decreased time of nonrapid eye movement (NREM) and rapid eye moveme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(45 citation statements)
references
References 41 publications
1
38
0
Order By: Relevance
“…Lateef and colleagues also found a statistically significant positive correlation between Internet addiction and insomnia among clinical medical students in Africa ( 52 ). We confirmed the H-01 and the role of melatonin could account for the relationship between smartphone overuse and sleep deprivation, which has been confirmed by animal and human studies ( 29 ). Melatonin is one of the hormones secreted by the pineal gland, which helps sleep and regulates the circadian clock ( 53 ).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Lateef and colleagues also found a statistically significant positive correlation between Internet addiction and insomnia among clinical medical students in Africa ( 52 ). We confirmed the H-01 and the role of melatonin could account for the relationship between smartphone overuse and sleep deprivation, which has been confirmed by animal and human studies ( 29 ). Melatonin is one of the hormones secreted by the pineal gland, which helps sleep and regulates the circadian clock ( 53 ).…”
Section: Discussionsupporting
confidence: 85%
“…In addition to the above psychological models, clinical mechanisms are beneficial to support our theoretical model regarding the relationship of PSU, sleep quality, and daytime fatigue. Blue light and electromagnetic radiation emitted by smartphones directly cause harm to users' eyesight, neck, and spine ( 14 , 29 ). Suppression of melatonin secretion caused by light stimulation at night is also a commonly recognized physiological pathway that results in sleep deprivation ( 30 ).…”
Section: Introductionmentioning
confidence: 99%
“…The impacts on zebrafish anxiety-related behavior are consistent with previous studies in rodent models that showed ongoing GHz or sub-GHz RFRs could alter behavior and sleep patterns. 6 , 15 While there was no direct correspondence between an abnormal larval behavior and an abnormal adult behavior, it is likely that the adult effects were manifestations of RFR impacts on development. Studies with embryonic neural stem cells have shown that RFR exposures can inhibit neural outgrowth that can potentially impact nervous system function in the long term.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, physical therapies have been used to treat chronic insomnia [ 4 , 5 ]. Electric, magnetic, and electromagnetic fields have been applied to modulate sleep in a series of clinical and experimental studies [ 6 , 7 , 8 ]. Most of these treatment approaches were non-invasive and less stimulant.…”
Section: Introductionmentioning
confidence: 99%